Budaya Politik Pemuda Batak di Jl. Taud Siderojo Kab. Deli Serdang (Studi terhadap Partisipasi Politik pada PILPRES 2024) - Jekson Saragih; Gadis Prasiska Sembiring; Ivana Theo Philia; Laras Sati Sintania; Nazlah Aulia; Reylan Silverius Sinaga; Salwa Andini; Prayetno Prayetno (Amandemen: Jurnal Ilmu pertahanan, Politik dan Hukum Indonesia, 2024)
In Indonesia, ethnic and cultural diversity provides its own color in the dynamics of political participation, including the Batak tribe which has unique cultural and social characteristics. Jl. Taud Siderojo in Deli Serdang Regency is one of the areas inhabited by the Batak community. The Batak people are famous for their spirit of togetherness (dalihan na tolu), courage and openness in expressing opinions. These cultural values ​​are very influential in various aspects of life, including politics. Batak youth in this region are not only the successors of tradition and culture, but also important actors in local and national political processes.